2005
DOI: 10.1002/hed.20275
|View full text |Cite
|
Sign up to set email alerts
|

Importance of tumor thickness and depth of invasion in nodal involvement and prognosis of oral squamous cell carcinoma: A review of the literature

Abstract: Authors are in substantial agreement regarding the reliability of tumor thickness. The lack of comparable study groups, measurement techniques, and cut-off values points to the need for further studies so as to reach a consensus and to develop therapy protocols that include tumor thickness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
293
1
7

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 358 publications
(309 citation statements)
references
References 77 publications
8
293
1
7
Order By: Relevance
“…In our study, the local recurrence rate of 10.3% was similar to those reported in the literature [5,13,[29][30][31]. Some studies have demonstrated that pathological variables such as DOI, surgical margin, and POI could be reliable parameters for local recurrence in early-stage OTSCC [8][9][10][11][20][21][22][23][24][25][26][27][28][29][30][31]. We observed that a higher incidence of local recurrence was associated with POI, NAC, closed surgical margin, and perineural invasion.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…In our study, the local recurrence rate of 10.3% was similar to those reported in the literature [5,13,[29][30][31]. Some studies have demonstrated that pathological variables such as DOI, surgical margin, and POI could be reliable parameters for local recurrence in early-stage OTSCC [8][9][10][11][20][21][22][23][24][25][26][27][28][29][30][31]. We observed that a higher incidence of local recurrence was associated with POI, NAC, closed surgical margin, and perineural invasion.…”
Section: Discussionsupporting
confidence: 88%
“…Treatment failure in OTSCC patients is most frequently due to local and regional recurrences [4,5]. The prognosis also depends or varies with nodal involvement, tumor thickness, and the status of the surgical margins [4][5][6][7][8][9][10][11]. In particular, the most significant prognostic factor in OTSCC is the presence of metastatic disease in the cervical lymph nodes [7,9,11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This was made possible by the adoption of a head and neck orthotopic model (Myers et al, 2002). This aspect is particularly relevant for head and neck cancer, as this type of cancer has a loco-regional evolution with frequent neck involvement, which is the most important parameter for prognosis (Pentenero et al, 2005). Of importance, the present data demonstrate a differential effect of the respective treatments on node involvement, lending additional clinical significance to the observations obtained from the examination of the primary tumours.…”
Section: Discussionsupporting
confidence: 61%
“…Several ways of defining TT have been used in the previous studies and summarized by Pentenero et al as follows: a) from surface/base of the ulcer to deepest point of invasion; b) from adjacent intact mucosa to deepest point of invasion; c) from basal membrane to deepest point of invasion. 18 Moore et al found that survival correlated better with TT when measured from a theoretical construction of a basement membrane through the tumor than from the surface of the tumor. 19,20 In a study originating from Tata Memorial Hospital, Mumbai, Kane et al compared depths measured from the surface of a tumor versus from adjacent normal mucosa and concluded that the latter (referred to as microscopic depth) had a stronger correlation with the risk of lymphnode involvement.…”
Section: Discussionmentioning
confidence: 99%